Mental Illness in Children - Rosemary Sheehan (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
In this Special Issue of Brain Sciences, we will be discussing "Mental Illness in Children" from a range of perspectives, exploring the prevalence and recognition of mental disorders in children, the types of disorders and approaches to meeting their needs, and the complexity and severity of mental health problems in children. We look to what models of care best respond to children's needs, the identification and management of risk, and the expertise needed to appropriately and effectively intervene when children need mental health care. We will welcome articles describing the range of issues that impact on mental disorder in children; models of intervention implemented and evaluated; new data on prevalence and nature of disorder; and critical reviews on mental health problems and vulnerability. We look forward to your valuable contribution to this Special Issue for this journal.